Evaluation of fly ash- and slag-based geopolymers for the improvement of a soft marine clay by deep soil mixing - Arulrajah, Arul; Yaghoubi, Mohammadjavad; Disfani, Mahdi Miri; Horpibulsuk, Suksun; Bo, Myint Win; Leong, Melvyn (Soils and foundations, 2018)
The use of deep soil mixing (DSM) in ground-improvement projects, for structures subjected to low to medium loads, has increased over the past decade due to its convenient and practical implementation and its economic advantages. Traditionally, Portland cement and lime have been the most popular binders for DSM applications. However, the ground-improvement industry has been keen to explore environmentally friendly alternatives with low carbon dioxide emission. The aim of this research is to investigate the use of two stockpiled industrial waste by-products, namely, fly ash (FA) and slag (S), as alternative green binders in ground-improvement projects that would reduce the carbon footprint of these projects. In this research, combinations of FA and S, activated by a liquid alkaline activator (L), were evaluated for the ground improvement of a soft marine clay, namely, Coode Island Silt (CIS). The performance of the FA + S geopolymers was compared with that of traditional cement and lime control binders. The soil moisture content was set at 0.75, 1.0 and 1.25 of the liquid limit (LL) of the soil to replicate the field conditions. 10, 20 and 30% binders, by dry soil mass, were added to the soil, and the samples were cured for 7 and 28 days. Unconfined compression strength (UCS), flexural beam and scanning electron microscopy (SEM) imaging tests were conducted to evaluate the changes in the engineering behavior and the microstructure of the mixtures. The results indicated that the strength and stiffness of the soft clay were significantly increased by the use of these new FA + S binders, which substantiated them as alternatives to traditional cement or lime binders. The optimum binder content was found to be 20%, while CIS + 5%FA + 15%S was found to be the optimum mixture. Furthermore, correlations between the UCS and the modulus of elasticity (E50) and between the UCS and the modulus of rupture (R) for the geopolymer mixtures were proposed. They will be valuable to both designers and practitioners of ground-improvement works.